2016
DOI: 10.5194/bg-13-1537-2016
|View full text |Cite
|
Sign up to set email alerts
|

Time since death and decay rate constants of Norway spruce and European larch deadwood in subalpine forests determined using dendrochronology and radiocarbon dating

Abstract: Abstract. Due to the large size (e.g. sections of tree trunks) and highly heterogeneous spatial distribution of deadwood, the timescales involved in the coarse woody debris (CWD) decay of Picea abies (L.) Karst. and Larix decidua Mill. in Alpine forests are largely unknown. We investigated the CWD decay dynamics in an Alpine valley in Italy using the chronosequence approach and the five-decay class system that is based on a macromorphological assessment. For the decay classes 1-3, most of the dendrochronologic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Herrmann et al [8] deduced from 5 sites on Luvisols, Cambisols, and Podsolic Cambisols that the decomposition rate was 88 years. Petrillo et al [57] calculated residence times of P. abies deadwood to 45, 56, and 84 years based on different methods on Cambisols, Umbrisols, and Podzols. Using the different approaches in our study, we found decomposition rates based on biomass loss for P. abies of 72 and 109 years.…”
Section: Decomposition Rates Of Downed Logsmentioning
confidence: 99%
“…Herrmann et al [8] deduced from 5 sites on Luvisols, Cambisols, and Podsolic Cambisols that the decomposition rate was 88 years. Petrillo et al [57] calculated residence times of P. abies deadwood to 45, 56, and 84 years based on different methods on Cambisols, Umbrisols, and Podzols. Using the different approaches in our study, we found decomposition rates based on biomass loss for P. abies of 72 and 109 years.…”
Section: Decomposition Rates Of Downed Logsmentioning
confidence: 99%
“…The latter includes the type of surrounding vegetation, altitude etc. (Müller et al 2015;Vrška et al 2015;Petrillo et al 2016;Chmura et al 2016;Staniaszek-Kik et al 2019). The colonization processes of plants and lichens on deadwood have been described in many studies since Hackiewicz-Dubowska (1936) and McCullough (1948) who were the first to identify the decomposition classes of logs and snags.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement of the protective role could last for a few years, before lying logs start to rot and the height of the logs from the ground starts to decrease, as observed in Wohlgemuth [12]. Moreover, with a reduction of deadwood height above the ground and with a higher portion of logs in direct contact with the soil, the wood decaying processes may accelerate [38], leading to lower protective efficiency of biological legacies.…”
Section: Discussionmentioning
confidence: 94%